Mair 2. Andrea McGuire interviews Jacqueline Mair, Witless Bay. - McGuire, Andrea (2014)
Andrea McGuire interviews Jacqueline Mair about the writing she does in her Witless Bay shed. 00:50 - Interpretations of various wall writings in interviewee's shed; Newfoundland and Scottish expressions; 03:58 - Discussion of expression, "peanut butter legs," invented by interviewee; 04:50 - Continues interpretations of wall writings; Newfoundland, Scottish and German expressions; 09:04 - Shed as social space for smokers; 10:22 - Discussion of specific wall utilized for writing